Detecting Innovators in the Field: Teachers’ Perceptions and Adoption of Generative AI in Education - Dalyanci, Alanur Ahsen; Mast, Lobke; Krushinskaia, Kristina; Raes, Annelies (The Open/Technology in Education, Society, and Scholarship Association Journal, 2025)
The adoption of Generative Artificial Intelligence (GenAI) has gained popularity since late 2022, sparking discussions about its role in education. An important issue is understanding teachers' perceptions of this technology, given that teachers are seen as key actors in integrating GenAI into teaching and learning processes. This qualitative research explores secondary school teachers' perceptions of GenAI, using an adapted Technology Acceptance Model (TAM) and Rogers' Diffusion of Innovation Model. TAM, known for assessing user acceptance of technology, was employed to gauge perceptions, while Rogers' model provided insights into how teachers distribute across GenAI adoption stages, from innovators to late adopters. Data was collected through semi-structured interviews and an online survey with 20 in-service teachers from Flanders, Belgium. Findings reveal mixed attitudes among teachers towards GenAI, as participants express enthusiasm about its potential for time-saving and personalized learning benefits, while also voicing significant concerns about plagiarism, GenAI’s trustworthiness, and its possible negative impact on students’ cognitive abilities. The study also highlights the current lack of sufficient training and support for teachers integrating GenAI.